Efeito do mercúrio sobre parâmetros bioquímicos e fisiológicos em pepino e milho: papel protetor do zinco - Cargnelutti, Denise (2009)
In this study, effects of mercury (Hg) in cucumber seedlings (Cucumis sativus L.) and maize (Zea Mays L.) hybrids, and Hg and Zn association in maize hybrids were investigated through the analysis of biochemical and physiological parameters. The biochemical parameters analyzed in C. sativus were: antioxidant enzyme activities (catalase (CAT), ascorbate peroxidase (APX) and superoxide dismutase (SOD)), and the non-enzymatic antioxidant levels (ascorbic acid (ASA), carotenoids, and non-protein thiol content (NPSH)). The thiobarbituric acid reactive substances (TBARS), chlorophyll, carbonyl protein, hydrogen peroxide (H2O2) contents and the δ-aminolevulinic acid dehydratase (δ-ALAD) activity were also determined. The growth of C. sativus was evaluated based on dry (DM) and fresh matter (FM), as well as on root and shoot length. Cucumber seedlings were exposed to 0 to 500 μM of HgCl2 for 10 and 15 days. The results showed that Hg was absorbed by the growing cucumber seedlings, and its content was greater in roots than in shoot. A reduction in root and shoot length was observed at all concentrations and time points tested. In the concentration of 50 μM HgCl2 root FM of 15-day-old seedlings increased, but it was reduced at the other concentrations. For 10-day-old seedlings, a reduction in root and shoot FM was observed. Regarding shoot DM, there was an increase at 500 μM on days 10 and 15, and in the concentration of 250 μM HgCl2 on day 15. Furthermore, a significant reduction in shoot DM at all tested concentrations was observed. The results showed higher levels of TBARS and carbonyl protein as well as a chlorophyll content reduction in seedlings exposed to 250 and 500 μM HgCl2. An increase in CAT and SOD activities, on days 10 and 15, respectively, exposed to 50 μM HgCl2 was observed, whereas at 500 μM HgCl2, there was a marked inhibition. An inhibition of APX enzyme at 250 and 500 μM HgCl2 on days 10 and 15 was observed. Moreover, 10-day-old seedlings presented H2O2 levels reduced at 250 JM HgCl2 and increased at 500 JM HgCl2. Non-enzymatic antioxidants such as NPSH, AsA and carotenoids were increased at all concentrations, except carotenoid levels, which were reduced at higher concentrations of HgCl2. δ-ALA-D activity increased at 50 JM HgCl2 on day 15, and was inhibited at higher concentrations. The effect of the metal toxicity in three maize hybrids, BR205, 30F71 and 32R21, in nutritive solution, was studied analyzing the following parameters after Hg exposure (0 100 JM Hg): growth, tissue Hg concentration and δ-ALAD activity. The results showed a higher uptake of Hg by maize hybrids, mostly in roots. The root and shoot growth was reduced at all tested concentrations. A similar response was also observed for DM and FM of roots and shoot. These hybrids showed inhibition in a dose-dependent manner in δ-ALA-D activity. However, 32R21 δ- ALA-D activity was inhibited by metal only at concentrations exceeding 50 JM Hg. The enzyme activity from 30F71 was not changed by Hg. In vitro studies showed that Hg inhibits the δ-ALA-D activity in a concentration-dependent manner and this inhibition was mixed. In order to investigate the antioxidant role of zinc under stress condition caused by Hg, the mechanisms of metal toxicity in two maize hybrids, BR205 e 32R21, in nutritive solution, were studied. The parameters analyzed in maize hybrids after 25 JM Hg and Zn (50, 100 and 200 JM Zn) exposures were: growth, tissue Hg and Zn concentrations, antioxidant enzymes activities (CAT, APX and SOD) and non-enzymatic antioxidants (AsA, NPSH and carotenoids). The H2O2 and carbonyl protein, δ-ALA-D activity and chlorophyll levels were also evaluated. The results of interaction between Hg and Zn indicated reduced Hg levels in treatments with 25 JM Hg + 50 JM Zn. Treatments using 25 JM Hg + Zn were effective in reducing the root carbonyl protein in 32R21, and H2O2 in BR205, increased by Hg exposure. Hg inhibited SOD and CAT activities in BR205 shoot, whereas APX activity was increased. However, Zn supplementation increased CAT and APX activities. In the 32R21, Hg reduced shoot APX activity and treatments with 25 JM Hg + 200 JM Zn increased its activity. Moreover, in vitro studies with Hg e/or Zn showed activation of antioxidant enzymes especially in the shoot. The results showed that Zn abolished the growth of maize hybrids which had been reduced by 25 JM Hg. The Hg reduced chlorophyll b content in maize hybrids, but only the concentration of 100 JM Zn was effective in restoring chlorophyll b levels. Treatments with Zn induced accumulation of NPSH, which was reduced by Hg exposure. Mercury induced a reduction in the growth and AsA levels from maize hybrids, and only the growth and fresh matter were restored by supplementation with Zn. Treatments with Hg inhibited δ-ALA-D activity from BR205, whereas supplementation with Zn at treatments with Hg restored the enzyme activity. However, in vitro studies showed that Zn did not prevent the inhibition of δ-ALAD activity caused Hg. Our results suggest that Hg induced oxidative stress in cucumber and maize seedlings. However, Zn has played an important role in fighting Hg toxicity, acting in ROS modulation and NPSH induction, allowing the growth of maize hybrids, even in the presence of Hg.